Methodological validation study of nrCE-SDS for monoclonal antibodies - Xu Gangling; Ni Yongbo; Wu Gang; Fu Zhihao; Yu Chuanfei; Wang Lan (生物医学转化)
Objective To perform methodological validation of non-reduced capillary electrophoresis-sodium dodecyl sulfate (nrCE-SDS) for monoclonal antibodies, providing a reference for the methodological validation of corresponding quality control methods in the industry. Methods Samples were analyzed according to the general chapter ＜3127＞ determination method for monoclonal antibody molecular size variants in the Pharmacopoeia of the People's Republic of China (2020 edition). Two laboratory technicians performed experiments over three days, using the same detection method daily to analyze the test samples, alongside comprehensive methodological validation. Results The method demonstrated good specificity, with the accuracy of the main peaks of all analytical samples reaching 98% to 102%, and the accuracy of total fragments and specific impurities reaching 70% to 130%. The relative standard deviation (RSD) for repeatability and intermediate precision was ≤15%. The ranges for the main peak, total fragment, and specific impurity were ≥89.9%, 0.66% to 10.10%, and 0.36% to 4.80%, respectively.The limit of quantification of the method was 0.33%. Conclusion Full validation demonstrates good accuracy, precision, linearity, range, limit of quantification, and specificity of the method, providing a reference for the scientific and rational design of corresponding methodological validations.